γ-oryzanol ameliorates the acute stress induced by behavioral anxiety testing in mice - Salina Akter; Hiroyuki Sasaki; Yuko Ikeda; Hiroki Miyakawa; Shigenobu Shibata (Elsevier, 2018)
We evaluated the anxiolytic effect of γ-oryzanol (GORZ) and elucidated the molecular mechanisms involved in its inhibition of behavioral test-induced anxiety. Behavioral tests were conducted on day 13, and mice were subjected to 30 min of acute restraint stress treatment (ARST) before sacrifice on day 16. In other group, behavioral tests were conducted on day 13 and 14 after ARST. 0.5% GORZ significantly weakened the effect of behavioral stress, but not the effect of strong ARST. GORZ downregulated ARST-induced cFos levels in the cerebral cortex. In conclusion, GORZ has potential ant-anxiety effect in the treatment of weak behavioral test-induced stress. Keywords: Anxiety, Behavioral tests, cFos